Surgical Management of Colonic Inertia - McCoy, Jacob A.; Beck, David E. (Clinics in Colon and Rectal Surgery, 2012)
For the select small number of constipated patients that cannot be managed medically, surgical options should be considered. Increases in our knowledge of colorectal physiology and experience have fostered improvements in patient evaluation and surgical management. Currently, patients with refractory colonic inertia are offered total abdominal colectomy and ileorectal anastomosis, often with laparoscopic techniques. With proper patient selection, the results have been excellent for resolving the frequency and quality of bowel movements. However, symptoms such as bloating and abdominal pain, which may be related to irritable bowel syndrome rather than the colonic inertia, may persist.
Keywords: constipation; colectomy; colonic inertia; abdominal pain